Coprophagia and Entomophagia in a Patient with Alcohol Related Dementia - Fonseca, João B.; Morgado, Pedro (Case Reports in Psychiatry, 2017)
Coprophagia and entomophagia are two phenomena not commonly reported in the medical literature and their occurrence is usually associated with mental disorders. We present the case of a 59-year-old man with a history of alcohol abuse who was evaluated due to cognitive deterioration and disturbed eating habits including feces and living insects. Organic causes were ruled out and an important cognitive impairment became evident on neuropsychological formal test. The behavior remitted after antipsychotic pharmacologic therapy and alcohol detoxification, leaving the diagnostic impression of alcohol related dementia. This report shows a rare association of these two conditions in a patient with dementia.